The Last Word: Balancing the Family Veto with a Legal Right to (Consent to) Donate Organs - Lazin, Sarah (Université d'Ottawa | University of Ottawa, 2024)
For many Canadians, the decision to register as an organ donor is made at the counter of ServiceOntario (or the provincial equivalent), and is reflected by a small notation on their driver's license. While most potential donors assume this registration carries binding legal effect, substitute decision-makers (SDMs) often invoke a "family veto”, whereby this previously expressed intention to donate organs is not honoured. This thesis takes up the following questions: (1) in what ways do current Canadian organ donation and transplantation (ODT) law, policy, and public health messaging (either intentionally or inadvertently) support the continued use of the family veto; (2) to what extent is the family veto contrary to Canadian ODT law; (3) how should Canadian ODT legislation be amended to reduce family veto events; and (4) whether there is a positive legal right to donate organs in Canada, or to consent thereto. Ultimately, this thesis aims to demonstrate how a legal right to donate organs (or, at a minimum, to consent to donation without interference) is supported by accepted legal, medical, and bioethical practice, but that it must be carefully constructed so as not to place healthcare providers in no-win situations when balancing patient autonomy with the desires of the living. Recognition of this right will, in turn, require a reshaping of donation consent frameworks, in law and in policy. For when it comes to donation after death, it is crucial that donors, families, and physicians alike have legal clarity on the question of who gets the last word.
Keywords: Organ Donation; Health Law; Organ Transplantation; Medical Law; Bioethics; Consent; Autonomy; Family Veto; Donor Registration; ODT